PELAKSANAAN PERJANJIAN PENYELESAIAN HUTANG ANTARA PT. DURI INDAH RAYA DENGAN PT. ADHI KARYA (PERSERO)Tbk - Hans M, Aryo Mitra; Hasanah, Ulfia; ', Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
The Implementation of a debt settlement agreement between PT. Duri Indah Raya and PT. Adhi Karya (Persero) Tbk begins with the debt of a cooperation agreement between both parties on the construction of Mall Duri . The payment that must be paid by PT. Duri Indah Raya is always less and late to PT. Adhi Karya and it makes the debt. Due to the debt, both parties agreed to finish it by converting a portion of the placement or placement into the PT. Adhi Karya Tbk by PT. Toward the effort to finish the debt between both parties, the problem is not resolved. The purpose of this study was to investigate the implementation of a debt settlement agreement between PT. Duri Indah Raya and PT. Adhi Karya, to determine what legal action can be taken to solve the problems of accounts payable of development cooperation agreements of PT Mall Duri between PT. Duri Indah Raya and PT. Adhi Karya. This type of research can is juridical empirical research, because in this study the authors directly conduct research on the location or place under study. From the research, there are two fundamental issues that will be concluded. Debts arising between PT. Duri Indah Raya and PT. Adhi Karya is preceded by the presence of a cooperation agreement between PT. Duri Indah Raya and PT. Adhi Karya Tbk about Duri Mall development. PT. Duri Indah Raya always late and less make payments on any payment. Then the parties agreed to settle the debt by converting a portion of the PT. Duri Indah Raya into placement or investment in shares of PT. Adhi Karya. However, the various efforts made by the parties, the debt still remains unresolved. Suggestions that there firmness of PT. Adhi Karya and if necessary legal measures both non-litigation and litigation to resolve their debt problems.Keywords: Implementation - Agreement - Debt Settlement